The role of virtual reality-based relaxation therapy in the treatment of mental disorders – a narrative review - Błażej Pilarski; Magdalena Stencel; Bartosz Bula; Szymon Florek; Robert Pudlo (Annales Academiae Medicae Silesiensis, 2025)
In recent years, there has been rapid development in technologies utilizing virtual reality (VR), leading to their increasingly frequent application in medicine, including psychiatry. Relaxation therapy using VR techniques may offer an innovative solution to support the treatment of mental disorders. This narrative review discusses the potential applications of VR in relaxation therapy, focusing on its effectiveness in treating depression, anxiety disorders, schizophrenia, and bipolar disorder. VR technology has been shown to offer significant advantages over traditional relaxation methods. Numerous studies confirm its effectiveness in reducing psychiatric symptoms, while also highlighting the need to consider potential side effects, such as nausea or “cybersickness”. VR therapy combines the benefits of technology and psychotherapy, making it a promising method for supporting the treatment of mental disorders.